Adeline and Julia : growing up in Michigan and on the Kansas frontier : diaries from 19th-century America - Graham, Adeline, 1864-1934 (Michigan State University Press, 2000)
The keeping of journals and diaries became an almost everyday pastime for many Americans in the nineteenth century. Adeline and Julia Graham, two young women from Berrien Springs, Michigan, were both drawn to this activity, writing about the daily events in their lives, as well as their ''grand adventures.'' These are fascinating, deeply personal accounts that provide an insight into the thoughts and motivation of two sisters who lived more than a century ago. Adeline began keeping a diary when she was sixteen, from mid-1880 through mid-1884; through it we see a young woman coming of age in t.